Knights and castles - Osborne, Will.; Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2000)
Jack and Annie look at knights, armor, and life in a castle.
"A nonfiction companion the The knight at dawn."
"A Stepping Stone book."
Includes bibliographical references and index.
RL: 2.9.
006-009.
690
Keywords: Knights and knighthood -- Europe -- Juvenile literature; Castles -- Europe -- Juvenile literature; Civilization, Medieval -- Juvenile literature; Middle Ages